Social Skill Training for Socially Isolated Patients: Concept Analysis - Suhermi Suhermi; Siti Linda Ariska; Asmi Asmi; Ika Aditya Wirawan; Edy Surya Pratama; Satriya Pranata; Siti Aisah; Aric Vranada (GLOBAL HEALTH SCIENCE GROUP, 2024)
Patients with social isolation are often found in psychiatric nursing practice, especially those with mental disorders such as schizophrenia, depression, or social anxiety disorder. Social isolation is someone who avoids social interaction and has difficulty communicating or building significant relationships with others. This condition greatly affects the patient's quality of life and worsens the symptoms of mental disorders experienced. The purpose of this concept analysis is to gain a more detailed and in-depth understanding of Social Skill Training in Socially Isolated Patients.This concept analysis uses the Walker and Avant approach with analysis steps including: utilization of attributes in case models, borderline cases, related cases, and opposite cases, explaining antecedents and consequences. Relevant literature findings related to the concept were obtained through concept databases such as Google Scholar, PubMed, Scopus, Science Direct, NCBI, Researchgate, Publish and Perish and ProQuest. Keywords used in the literature search include